Coping e rede social pessoal de mães de crianças diagnosticadas com a Síndrome Congênita do Vírus Zika - Pequeno, Vanessa Cavalcante (2019)
Congenital Zika Virus Syndrome (SCVZ) is a recent problem in the history of health in Brazil, and arises in a context of socioeconomic vulnerability, especially in the Northeast region of the country, especially in the State of Paraíba, affecting children with various complications that alter the development, including microcephaly. The seriousness of this problem combined with the novelty character contributes to the potentiation of stress before the situation, which makes the coping process more difficult, which presupposes the need for assistence through supportive relationships that support fathers and, especially mothers, as the main caregivers. In this perspective, through a qualitative descriptive and exploratory research, from April to December 2018, carried out in the interior of the state of Paraíba in a Specialized Rehabilitation Center the objective of this report was to analyze the Coping Strategies and the Personal Social Network of mothers of children affected by Congenital Zika Virus Syndrome. The data collection instruments used were sociodemographic form and semi-structured interview with the insertion of the Network Map and based on the Coping Motivational Theory. The process of systematization and data analysis was carried out through the analysis of categorial thematic content and the results were presented in two articles that interconnect with each other. The first deals with the Personal Social Network in the context of the syndrome and the second addresses the Coping strategies used by the participants in the context of motherhood before of this syndrome. The data allow a better understanding of this problem, showing that most of the mapped networks are small, located mainly in the family and health services quadrants, with emotional support and material and service assistence as main functions. In addition, the most used coping strategy, given the situation as a whole, was the search for comfort, linked to religiosity, also evidenced in the significant relationships of the participants Network and point to the need to expand access for children and their mothers to health services and resources made available by the government, for greater investment in the training of professionals and in material support for families as a constitutional right. Finally, the experience of motherhood in the context of SCVZ, requires individual and collective efforts to overcome the immense challenges. The Personal Social Network becomes effective, in this context, by allowing the involvement of its members and triggering significant support links to mothers. Coping strategies also play an important role in developing the ability to overcome adverse situations. In this context, the network constitutes an important social support for mothers in the development of strategies to face the challenges before which they stand out, showing signs of resilience.